REMOVAL OF POLYCYCLIC AROMATIC HYDROCARBONS AND CHEMICAL OXYGEN DEMAND FROM PRODUCED WATER USING NANOSCALE ZERO-VALENT IRON AND FERRATE (VI) OXIDATION - HANEEF, TAHIR (2021)
Wastewater obtained during oil and gas extraction process known as produced water (PW), it is a byproduct of oil and gas extraction industries. It holds a large amount of hazardous non-biodegradable organic compounds especially polycyclic aromatic hydrocarbon (PAHs) (40-3000 μg/L) and chemical oxygen demand (1220-2600 mg/L). The main objective of this study is to investigate the effectiveness of two AOPs separately i.e. as nano scale zero valent iron (nZVI)-Fenton oxidation and Ferrate (VI) oxidation for the removal of PAHs and chemical oxygen demand (COD) from PW.